Glaucoma is associated with plasmin proteolytic activation mediated through oxidative inactivation of neuroserpin - Gupta, Vivek (Sci Rep, 2017)
Neuroserpin is a serine protease inhibitor that regulates the activity of plasmin and its activators in the neuronal tissues. This study provides novel evidence of regulatory effect of the neuroserpin on plasmin proteolytic activity in the retina in glaucoma. Human retinal and vitreous tissues from control and glaucoma subjects as well as retinas from experimental glaucoma rats were analysed to establish changes in plasmin and neuroserpin activity. Neuroserpin undergoes oxidative inactivation in glaucoma which leads to augmentation of plasmin activity. Neuroserpin contains several methionine residues in addition to a conserved reactive site methionine and our study revealed enhanced oxidation of Met residues in the serpin under glaucoma conditions. Met oxidation was associated with loss of neuroserpin inhibitory activity and similar findings were observed in the retinas of superoxide dismutase (SOD) mutant mice that have increased oxidative stress. Treatment of purified neuroserpin with H2O2 further established that Met oxidation inversely correlated with its plasmin inhibitory activity. Dysregulation of the plasmin proteolytic system associated with increased degradation of the extracellular matrix (ECM) proteins in the retina. Collectively, these findings delineate a novel molecular basis of plasmin activation in glaucoma and potentially for other neuronal disorders with implications in disease associated ECM remodelling.